The Role of Scientific Literacy in Climate Change-Based Science Learning: A Literature Review - Gesti Maharani; Melani Aulia Hatami (Indonesian Journal of STEM Education, 2025)
This study aims to examine the strengthening of students’ scientific literacy through science learning that integrates climate change issues. The method employed was a narrative literature review by analyzing national and international articles published between 2019 and 2025 that are relevant to scientific literacy, science education, and issue-based learning approaches. The findings indicate that the integration of climate change issues, particularly through the Socio-Scientific Issues (SSI) approach, enhances conceptual understanding, data analysis skills, scientific argumentation, and evidence-based decision-making. Learning innovations such as climate flashcards, science gardens, digital modules, and the use of AR/VR technologies contribute to increased student engagement and data literacy. Overall, issue-based science learning that incorporates climate change has proven effective in developing students’ scientific literacy and environmental awareness. This review recommends the development of more contextual and sustainability-oriented learning strategies.